Measurements of radon gas concentration in surface soil in Baghdad city - Ola Adil Ibrahim (Iraqi Journal of Physics, 2018)
In the present work, radon gas concentrations in different surface soil samples in Baghdad governorate were measured using RAD-7 detector. The results have been shown that, the Radon gas concentrations ranged between (41.67±1.78Bq/m3), to (185.67±4.22Bq/m3), a map showing the distribution of the concentration of radon in selected areas was defined to identify areas with high pollution level. The reason for the high concentration of radon is that these surface soil samples are taken from agricultural areas. It is also known that fertilizers contain uranium levels as well as areas bombed in wars in the country. It is worth noting that all radon concentrations in Baghdad governorate are below the recommended minimum of 200-300Bq/m3) (International Commission on Radiation Protection, ICRP, 2009).